The Law of the Jungle. The Online Hate-speech against the Roma in Romania. Issue 8 (17th November 2021) - Molnar, Lorena
ABSTRACT: The Roma people are the largest minority in Europe and, since centuries, have suffered discrimination and hate crimes which persist currently. This paper analyzes 4, 136 comments (2016–2020) about the Roma posted on an online open-access forum. Our findings suggest that the factors influencing Romanians' hostility against the Roma are: (1) the general distrust in the Romanian administrations, (2) the feeling of threat, and (3) the in-group favoritism. The article discusses strategies such as the improvement of the citizens' trust in the public administration, pragmatic interventions bottom-up which aim to increase the social pacification, the redefinition of the political correctness, and the application of situational prevention techniques to prevent hate crimes.